An hybrid design solution for spacecraft simulators - Vítor Rodrigues (2008)
The European Space Agency (ESA) has created the Simulation Model Portability 2 (SMP2) standard with the purpose to provide a design solution for the project of Spacecraft Simulators. One element of the SMP2 standard is the metamodel Simulation Model Definition Language (SMDL). The design artefacts of a Spacecraft Simulator consist in descriptions of the business logic shared by a set of SMP2 models. This paper reports results from a study that considers the hypothesis to complement the model-driven design approach of the SMP2 standard with test-driven design techniques. The high-level abstractions of Spacecraft Simulators are used to carry out Model-Driven Development processes, while reusable pieces of software that can to be used by many SMP2 models are designed and developed following Test-Driven-Development. The tool capable to establish the dependencies between the source code produced by the two methodologies and mission specific source code is the GNU Build System.